Crack initiation and life estimation for 316 and 430 stainless steel specimens by means of a critical plane approach. (September 2020) - Vantadori, Sabrina; Carpinteri, Andrea; Luciano, Raimondo; Ronchei, Camilla; Scorza, Daniela; Zanichelli, Andrea; Okamoto, Yuki; Saito, Shunsuke; Itoh, Takamoto
Highlights: The fatigue behaviour of both 316 and 430 stainless steel specimens is analysed. The multiaxial critical plane-based criterion by Carpinteri et al. is used. Triaxial loadings with a constant amplitude, under HCF regime, are considered. Analytical results are compared with experimental ones in terms fatigue lifetime. Critical plane orientations are compared with experimental initial crack orientations. Abstract: In the present paper, the fatigue behaviour of two stainless steels is analysed by employing the criterion by Carpinteri et al. Such a criterion has already been applied to many data related to different metals, but the novelty of this paper is its application to assess the results of experimental tests performed under HCF triaxial loading. Such experimental data, found in the literature, are related to hollow cylindrical dog-bone specimens made of both 316 and 430 stainless steel. The experimental results are compared with the analytical ones in terms of both fatigue lifetime and initial crack plane orientation.